Concentrations of neonicotinoid insecticides in honey, pollen and honey bees (Apis mellifera L.) in central Saskatchewan, Canada. (February 2016) - Codling, Garry; Al Naggar, Yahya; Giesy, John P.; Robertson, Albert J.
Abstract: Neonicotinoid insecticides (NIs) and their transformation products were detected in honey, pollen and honey bees, ( Apis mellifera ) from hives located within 30 km of the City of Saskatoon, Saskatchewan, Canada. Clothianidin and thiamethoxam were the most frequently detected NIs, found in 68 and 75% of honey samples at mean concentrations of 8.2 and 17.2 ng g −1 wet mass, (wm), respectively. Clothianidin was also found in >50% of samples of bees and pollen. Concentrations of clothianidin in bees exceed the LD50 in 2 of 28 samples, while for other NIs concentrations were typically 10–100-fold less than the oral LD50 . Imidaclorpid was detected in ∼30% of samples of honey, but only 5% of pollen and concentrations were <LOD in bees. Transformation products of Imidaclorpid, imidaclorpid-Olefin and imidacloprid-5-Hydroxy were detected with greater frequency and at greater mean concentrations indicating a need for more focus on potential effects of these transformation products than the untransformed, active ingredient NIs. Results of an assessment of the potential dietary uptake of NIs from honey and pollen by bees over winter, during which worker bees live longer than in summer, suggested that, in some hives, consumption of honey and pollen during over-wintering might have adverse effects on bees. Highlights: Pollen, honey and worker bees were extracted by modified QuEChERS method for neonicotinoid insecticides and metabolites. Samples collected within a 30 km of the city of Saskatoon indicate the variability inherent within even a short distance. Concentration of clothianidin and thiamethoxam based on published LD50 values, exceeded the lowest values in 2 Bee samples. Imidacloprid metabolite concentrations were at greater concentration than their parent molecule. Over winter concentration estimate that dietary intake may impact bee health.